2010
DOI: 10.1088/0264-9381/27/14/145010
|View full text |Cite
|
Sign up to set email alerts
|

Extra polarization states of cosmological gravitational waves in alternative theories of gravity

Abstract: Cosmological Gravitational Waves (GWs) are usually associated with the transverse-traceless part of the metric perturbations in the context of the theory of cosmological perturbations. These modes are just the usual polarizations '+' and '×' which appear in the general relativity theory. However, in the majority of the alternative theories of gravity, GWs can present more than these two polarization states. In this context, the Newman-Penrose formalism is particularly suitable for evaluating the number of non-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 40 publications
2
41
0
Order By: Relevance
“…In conclusion 18 , any metric formulation of f (R) leads to the existence of four polarization modes. This is thus in agreement with the results obtained via the NP approach 13,14 and clarifies the disagreement found so far in several papers in the recent literature.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In conclusion 18 , any metric formulation of f (R) leads to the existence of four polarization modes. This is thus in agreement with the results obtained via the NP approach 13,14 and clarifies the disagreement found so far in several papers in the recent literature.…”
Section: Resultssupporting
confidence: 93%
“…Another powerful tool to study the properties of GW in any metric theory is the Newman-Penrose formalism (NP) 11,12 . The polarization of GW has been investigated using this approach, 13,14 and it was shown that scalar-tensor and f (R) theories both present two additional scalar modes: a longitudinal and a breathing mode. Therefore, there seems to be a disagreement between the linearized and the NP approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In GR, a GW has two polarization modes (plus and cross modes), while in a general metric theory of gravitation, the GW is allowed to have at most six polarizations [9,10]. In modified gravity theories such as the scalar-tensor theory [11,12] and f (R) gravity [13,14], additional scalar polarizations appear (For more rigorous treatment of the polarizations with the Newman-Penrose formalism, see [15,16]). On the other hand, in bimetric gravity theory [17] and massive gravity theory [18,19], there appear at most six and five polarization modes, respectively, including scalar and vector modes [16,20].…”
Section: Introductionmentioning
confidence: 99%
“…Among the proposed theories, scalar-tensor theories predict GWs with one or two polarization modes with helicity s = 0 besides the two usual modes with helicity s = ±2 [4,5]. Also theories that introduce geometrical corrections in the Einstein-Hilbert Lagrangian have appeared in the literature.…”
Section: Introductionmentioning
confidence: 99%